An Explorative Investigation of the Warm-up Practices of Professional and Amateur Rugby League Players - Ryan A. Morrow; Daniel C. Bishop; Thomas I. Gee (International Universities Strength and Conditioning Association, 2020)
This study aimed to assess warm-up practices within professional and amateur Rugby League players, specifically to determine players' perceptions why particular methods were used and discover whether any differences existed in warm-up practices and perceptions between the two separate standards. The study used a 10 question online questionnaire to investigate 30 professional and 53 amateur players warm-up protocols and their perceptions behind their practices. To provide a richer understanding regarding the practices and perceptions surrounding warm-up protocols, the questionnaire was followed by two focus groups (professionals and amateurs), which included four participants in each. Following analysis of the questionnaire responses, it was discovered that professional players warm-up protocols were significantly longer in duration than amateur players (P = 0.009). However, for all other variables assessed including; specific warm-up protocols, static stretch duration, and perceptions and beliefs concerning warm-up protocols, there were no significant differences between professionals and amateurs. Overall findings demonstrated the widespread use of static stretching within warm-up for both professionals and amateurs; 71 of 83 players (86%) reported usage. It was also highlighted that injury prevention was the most commonly perceived benefit from performing a warm-up across both standards [(Professional; 15 of 30, 50%) (Amateur; 27 of 53, 51%)]. Findings from the focus group generally supported questionnaire responses, and it was identified that the warm-up practices and protocols of Rugby League players were influenced by others such as coaches and strength and conditioning coaches which emphasises the importance of the role such practitioners.